Rethinking the institution of masjid as a community development center in Bangladesh - Asif, Nayeem; Utaberta, Nangkula; Ismail, Sumarni; Sabil, Azmal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2024)
The institution of masjid (mosque) acted as the center of activities of Muslim communities for centuries. Until now, masjid has been a significant establishment within any Muslim community. Nevertheless, today's masjids are not involved with society and not as active as they were during the early age of Islam. In Bangladesh for particular, where 86 of the population is Muslim, the institution of masjid is merely utilized as a place of worship, devoid of any community development activity. This study aims to identify the factors behind the idleness of masjid institutions within Muslim communities in Bangladesh and proposes recommendations to improve the situation. There is so much potential to utilize the existing masjids as a center for community development by extending the scope of activities with the participation of the community members. This study compiled and analyzed the opinions of previous researchers regarding this issue and formulated queries to conduct semi-structured interviews among selected respondents. Experts and professionals were interviewed to evaluate the current scenario regarding this topic and compile recommendations proposed by them. By analyzing the results through descriptive analysis, this study concluded that several factors are responsible for the idleness of masjids in Muslim communities. Inefficient management, absence of income-generating schemes, exclusion of certain social groups, and inadequate facilities are the significant factors identified by this study. Some minor factors were also identified, and recommendations were made based on all of these factors. It is highly recommended that these institutions be fully utilized to develop their surrounding communities. The findings are crucial to rethink the role of the institutions of masjid as a significant catalyst for community development in the Muslim communities in Bangladesh